الحكم الرشيد في فتاوى العلامة الشيخ محمد أبو زهرة - Makki (مجد مكي) Majd (At-Tajdid - Intellectual Refereed Journal, 2018)
Abstract This paper aims to outline the meaning of good governance from the fatwas and views in the policies based on the Islamic sources by Syeikh Muhammad Abī Zahrah. He has a significant role in this aspect of knowledge and was very instrumental in calling for it to fight corrupted governance and dictatorial tyranny as well as to uncover the negative trends in Islamic governance and society. The researcher uses analytical deductive method to find these aspects in the fatwās of the Syeikh. It concludes with some observations, among which are; that the Islamic state – according to the definition of the Syeikh – is a country where a Muslim feels that his life and property are safe under the rule of Islam; the pillars of good governance are justice, consultation among the ruling members (Syūra), implementing the rules in Quran and Sunnah and common interest. Keywords: Good governance, Fatwās, Muhammad Abū Zahrah, Islamic state